The Challenges of Junior High School Students in Solving Fraction Problems Based on Newman's Error Analysis - Doni, Petrus Kanisius Nama; Prabawanto, Sufyani (FKIP Universitas Lampung, 2025)
This study aims to analyze the type of errors made by eighth-grade students in solving fraction problems at a public junior high school in Lembata Regency, East Nusa Tenggara. The analysis was conducted using the Newman Error Analysis (NEA). The research employed a qualitative descriptive method with nine eighth-grade students as the subjects. The instruments used included a written test consisting of 17 questions and interview guidelines based on the five stages of error identified in NEA: reading, comprehension, transformation, process skills, and encoding. The analysis revealed no errors in the reading stage, indicating that students were generally able to read and extract relevant information from the problems correctly. However, significant errors began to appear in the subsequent stages. In the comprehension stage, 16.84% of students failed to interpret the question correctly or misunderstood essential information, potentially leading to incorrect solution steps. Transformation errors occurred in 26.94% of cases, where students struggled to convert verbal information into a mathematical representation. In the process skills stage, 27.27% of students made mistakes in performing basic mathematical operations, such as fraction calculations. The highest error rate was observed in the encoding stage, where 28.96% students were unable to correctly write the final answer, even after processing the question appropriately. These findings indicate that students face difficulties not only in conceptual understanding but also in procedural fluency and mathematical expression. Keywords: difficulty, fraction, newman error analysis, process skills, encoding.